MENINGKATKAN AKSES PENDIDIKAN MELALUI PENDIDIKAN KESETARAAN NON-FORMAL: STUDI DI PUSAT PEMBELAJARAN MASYARAKAT DI INDONESIA - Laila Utyani Putri; Al Jannah Fadillah; Pusva Diana Sari; Shofiya Ajeng Pratiwi; Bimo Samudro (Journal Education for All: Media Informasi Ilmiah Bidang Pendidikan Luar Sekolah, 2025)
Access to education remains a critical challenge in Indonesia, particularly for individuals who are unable to complete formal schooling due to socio-economic and personal constraints. Non-formal education, especially through community learning centers, plays a strategic role in addressing this issue by providing flexible and inclusive learning opportunities. This study aims to examine the implementation of non-formal equivalency education in enhancing educational access for learners at a community learning center, PKBM Mutiara Bintang. This research employs a qualitative descriptive approach, with data collected through observations, in-depth interviews, and documentation. The findings reveal that the implementation of equivalency education has significantly contributed to expanding educational access by accommodating diverse learner backgrounds, fostering active and supportive learning environments, and promoting learner motivation. In addition, the program not only facilitates the acquisition of basic academic knowledge but also equips learners with practical skills relevant to everyday life. The study highlights that flexibility, inclusivity, and learner-centered approaches are key factors in the effectiveness of non-formal education programs. These findings suggest that equivalency education can serve as an adaptive strategy to reduce educational inequality and support lifelong learning opportunities.